2020
DOI: 10.1016/s2213-2600(20)30363-5
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of asthma and the promise of genomics-guided drug target discovery

Abstract: Asthma is an inflammatory airway disease that is estimated to affect 339 million people globally. The symptoms of about 5-10% of patients with asthma are not adequately controlled with current therapy, and little success has been achieved in developing drugs that target the underlying mechanisms of asthma rather than suppressing symptoms. Over the past 3 years, well powered genetic studies of asthma have increased the number of independent asthmaassociated genetic loci to 128. In this Series paper, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 116 publications
2
112
0
4
Order By: Relevance
“…9 . Notably, 101 of them overlapped with the recent list of 161 possible asthma drug targets summarized by El-Husseini et al 20 , which were derived from eQTL and non-synonymous analysis of independent variants associated with asthma in previous GWAS (Supplementary Data 17 ). According to the Open Targets Platform 21 , 13 out of 806 are the targets of investigational or approved asthma drugs (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…9 . Notably, 101 of them overlapped with the recent list of 161 possible asthma drug targets summarized by El-Husseini et al 20 , which were derived from eQTL and non-synonymous analysis of independent variants associated with asthma in previous GWAS (Supplementary Data 17 ). According to the Open Targets Platform 21 , 13 out of 806 are the targets of investigational or approved asthma drugs (Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 3 years, the number of independent asthma‐associated genetic loci has increased to 128 according to well‐powered genetic studies. 81 In a post hoc analysis of the DREAM and MENSA study, genetic markers were tested in patients with severe asthma and found no genetic associations related to response to mepolizumab, even though it cannot be excluded the possibility of the existence of rare genetic variants not yet explored predictive of response. 80 Further studies are needed to establish the functional significance of gene variants associated with asthma and potential genetic biomarkers indicators of response to anti‐IL5/IL5R mAbs still need to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…GPP65 encodes the chief acid-sensing receptor, G protein-coupled receptor 65 (GPR65), which increased the cellular viability of eosinophils in allergic airway inflammatory settings in mice [ 134 ]. Interestingly, the GWAS study for ACO and COPD failed to identify known asthma-associated genetic loci such as ORMDL3 , IL1RL1 and IL4R [ 135 ], indicating that ACO was not just an overlapping condition of asthma and COPD but was associated with a specific genetic background independent of asthma or COPD.…”
Section: Discussionmentioning
confidence: 99%